1979
DOI: 10.1111/j.1365-2141.1979.tb03693.x
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryoblastic Leukaemia (Acute Myelofibrosis): a Report of Three Cases

Abstract: Three patients with megakaryoblastic leukaemia are described. All three presented with pancytopenia, a few blast cells in the peripheral blood and absence of overt hepatosplenomegaly. In two of them bone marrow aspiration yielded a dry tap. Histological investigation of the bone marrow indicated that the megakaryocytic cell line was the dominant proliferating lineage. Cytochemical and EM investigation supported these findings. The isomorphic isoenzyme pattern of the elevated serum lactic dehydrogenase might be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Some believe that it is a variant of AML, and consider it to be equivalent to AMKL. 8,[18][19][20][21] Yet others believe that it is an acute variant of MDS, 22-24 a group of disorders in which myelofibrosis can also be observed. 25,26 The primary differential diagnosis of APMF is, however, with AMKL.…”
Section: Discussionmentioning
confidence: 99%
“…Some believe that it is a variant of AML, and consider it to be equivalent to AMKL. 8,[18][19][20][21] Yet others believe that it is an acute variant of MDS, 22-24 a group of disorders in which myelofibrosis can also be observed. 25,26 The primary differential diagnosis of APMF is, however, with AMKL.…”
Section: Discussionmentioning
confidence: 99%
“…There is also some controversy about the relationship of APMF to acute megakaryoblastic leukemia. 58,59 The WHO committee recognized this problem. If the leukemia is predominantly megakaryoblastic with myelofibrosis, we suggest the term "acute megakaryoblastic leukemia with myelofibrosis."…”
Section: Org Frommentioning
confidence: 99%
“…Several investi gators have described single cases of myelofibrosis with a unique terminal picture with thrombocytosis, giant plate lets and abnormal mononuclear cells in the circulation difficult to characterize on a morphological basis only. Published pictures of those 'atypical blastic cells', are con sistent with megakaryocytic precursors and micromega karyocytes [4,10,11,16].…”
Section: Discussionmentioning
confidence: 99%
“…Myelofibrosis with myeloid metaplasia has been fre quently described as a complication of patients with essential thrombocythemia and this probably represents the natural course of myeloproliferative disorders involv ing the megakaryocytic lineage [4][5][6][7][8][9][10][11][12][13][14][15][16][17], Reilly [18] has recently reviewed the pathogenesis of the so-called idio pathic myelofibrosis and concluded that the fibroblast proliferation is a reactive process secondary to the un derlying clonal hematopoiesis and not, as previously thought, a primarily malignant fibroblastic disorder. Us ing G6PD isoenzyme analysis it has been demonstrated that the fibroblast proliferation is a polyclonal process in response to megakaryocytic or myeloid-produced factors [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation